2017
DOI: 10.4172/2161-0495.1000355
|View full text |Cite
|
Sign up to set email alerts
|

Oral Glycine and Sodium Thiosulfate for Lethal Cyanide Ingestion

Abstract: Objective: Accidental or intentional cyanide ingestion is an-ever present danger. Rapidly acting, safe, inexpensive oral cyanide antidotes are needed that can neutralize large gastrointestinal cyanide reservoirs. Since humans cannot be exposed to cyanide experimentally, we studied oral cyanide poisoning in rabbits, testing oral sodium thiosulfate with and without gastric alkalization. Setting: University research laboratory.Subjects: New Zealand white rabbits.Interventions: Seven animal groups studied; Groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…[2][3][4]14,[24][25] Future studies should evaluate promising countermeasures in our swine model-similar to what has been done for intravenous KCN models-in experiments that reflect clinically relevant scenarios. 3,4,7,8 Our study has limitations. This study was a pilot study, and the sample size was small.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…[2][3][4]14,[24][25] Future studies should evaluate promising countermeasures in our swine model-similar to what has been done for intravenous KCN models-in experiments that reflect clinically relevant scenarios. 3,4,7,8 Our study has limitations. This study was a pilot study, and the sample size was small.…”
Section: Discussionmentioning
confidence: 94%
“…In particular, the authors used continuous-wave near-infrared tissue spectroscopy system to monitor for toxicity in real-time and found that a combination of oral glycine and sodium thiosulfate may be useful for treating high-dose acute cyanide ingestion. 7 The authors highlighted the difference between the metabolic rates of rabbits and humans as a limitation of using rabbits for these types of studies. Of the 2 species, rabbits have a higher metabolic rate, and this difference has implications regarding the toxicokinetics of oral poisonings, time window for antidote administration, and response to potential oral antidotes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our model does allow for invasive assessment of clinically relevant parameters. While most cases of cyanide toxicity result from ingestion or inhalation, we chose intravenous administration of potassium cyanide in an effort to induce reproducible, predictable, controlled, and rapid toxicity [2,3,12,17,18,20]. Intravenous administration minimizes the risk to research staff compared to the inhaled route.…”
Section: Limitationsmentioning
confidence: 99%
“…80 Robust research is under way to develop antidotes that have higher potency or that may be given intramuscularly or orally in the case of mass casualties (e.g., cobinamide, a hydroxocobalamin congener; sulfanegan, a sulfate donor; intramuscular nitrite and thiosulfate; and oral glycine or thiosulfate). 72,81,82 Hydrogen sulfide also binds to methemoglobin and cobalt compounds, and patients may benefit from the prompt administration of nitrite (without thiosulfate) or hydroxocobalamin. 58 In addition, cobinamide was shown to have antidotal efficacy on the toxic effects of hydrogen sulfide in a study in animals.…”
mentioning
confidence: 99%